Assessing the effect of Provitamin A on maize field resistance to aflatoxin and fumonisin contamination - Mboup, M.; Aduramigba-Modupe, A.O.; Olasanmi, B.; Mengesha Abera, W.; Meseka, S.K.; Dieng, I.; Menkir, A.; Ortega-Beltran, A. (Elsevier, 2024)
Vitamin A deficiency in sub-Saharan Africa is mainly being addressed through crop biofortification. Several high provitamin A (PVA) maize varieties have been released as part of these measures. However, these varieties are grown in areas where Aspergillus ear rot (AER) and Fusarium ear rot (FER) frequently occur, leading to contamination with mycotoxins, which in turn reduce the yield and grain quality. Chronic mycotoxin exposure leads to serious public health problems. Therefore, PVA maize varieties should be resistant to mycotoxin contamination. In a previous study, we generated 120 PVA hybrids by crossing 60 PVA inbreds and two testers with contrasting PVA content. Several inbreds resistant to aflatoxin were detected through laboratory-based kernel screening assays. In the current study, 21 PVA inbred lines with varying carotenoid content inoculated with toxigenic isolates of A. flavus and F. verticillioides were evaluated in field trials conducted at two locations in Nigeria for resistance to ear rots and mycotoxin production. Inbred lines resistant to AER, FER, aflatoxin and fumonisin contamination were identified. High PVA inbred lines were less susceptible to the ear rots, aflatoxin, and fumonisin than those with low PVA content. There were negative correlations between PVA content and each of AER (r = −0.28, P < 0.0001), FER (r = −0.37, P < 0.0001), aflatoxin (r = −0.15, P < 0.05), and fumonisin (r = −0.27, P < 0.0001). Three promising inbred lines were resistant to both aflatoxin and fumonisin. Moreover, the inbred TZI1715 combined resistance to AER, FER, aflatoxin, and fumonisin with desirable general combining ability for high β-carotene and total PVA content. These results suggest that the PVA biofortified maize developed to address vitamin A deficiency can also contribute to reduced exposure to aflatoxin and fumonisin.